2023
DOI: 10.3390/ijms24065868
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Selection Signature Analysis of Chinese Gamecocks Based on Genomic and Transcriptomic Data

Abstract: Selection pressures driven by natural causes or human interference are key factors causing genome variants and signatures of selection in specific regions of the genome. Gamecocks were bred for cockfighting, presenting pea-combs, larger body sizes, stronger limbs, and higher levels of aggression than other chickens. In this study, we aimed to explore the genomic differences between Chinese gamecocks and commercial, indigenous, foreign, and cultivated breeds by detecting the regions or sites under natural or ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…There is evidence indicating that DGKB significantly influences glucose metabolism ( Renstrom et al, 2011 ; van de Bunt et al, 2015 ) and has also been found to be associated with fat deposition ( Xing et al, 2019 ). Recent research has indicated that DGKB has been identified through GWAS as potentially related to bone and muscle development in Chinese gamecocks populations ( Ren et al, 2023 ). Regarding CTNNA2 , it has been reported to be associated with milk fat production in cows ( Laodiim et al, 2023 ) and is also implicated in lipid metabolism ( Schooling, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence indicating that DGKB significantly influences glucose metabolism ( Renstrom et al, 2011 ; van de Bunt et al, 2015 ) and has also been found to be associated with fat deposition ( Xing et al, 2019 ). Recent research has indicated that DGKB has been identified through GWAS as potentially related to bone and muscle development in Chinese gamecocks populations ( Ren et al, 2023 ). Regarding CTNNA2 , it has been reported to be associated with milk fat production in cows ( Laodiim et al, 2023 ) and is also implicated in lipid metabolism ( Schooling, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic may be related to the aggressive nature of this breed. After long-term artificial selection, Henan Gamecocks have developed different muscle distributions from other breeds [ 29 ]. Compared with broiler chickens, Henan Gamecocks have a stronger metabolism to support their activities of moving faster and fighting with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, domestic chickens are desirable models for investigating genetic adaptation and diversity and disease-related markers due to the advantages of their short reproductive cycle, small body size, and identical ancestors. After domestication from red jungle fowl (Gallus gallus spadiceus) 8 , chickens were cultivated with the aim of meeting various human demands, and meat-type (e.g., Xiaoshan chicken), egg-type (e.g., Xianju chicken), ornamental-type (e.g., Silkie chicken), and game fowl breeds (e.g., Luxi gamecocks, Henan gamecocks) were developed [9][10][11][12] , as well as the commercial broilers (e.g., broiler line B, Cobb) 13 . Therefore, it is relatively easy to unambiguously infer the driving factors of phenotypic or behavioural changes in these chickens.…”
Section: Background and Summarymentioning
confidence: 99%